Technology Teacher Trainees' Lesson Planning Approach in South Africa: Room for Improvement. Issue 3 (2nd September 2017) - Kola, Malose Isaac
Abstract : Technology education in South Africa provides learners with the opportunity to, inter alia, solve problems by applying creative skills using authentic contexts that are embedded in real-life situations. Effective lesson planning is rather imperative in exploiting this opportunity. The design process is considered to be the backbone of teaching technology and should be organised in such a way that all technology aims are achieved. This study, guided by John's framework for the lesson planning process, followed a qualitative approach to obtain a deeper understanding of the process that teacher trainees undertake while preparing their lesson plans during their teaching practice. Data was collected through open-ended questions, as well as the lesson plans that the teacher trainees developed during their teaching practice. The findings show that the teacher trainees battled to incorporate the design process when planning their lessons. In addition, they selected teaching methods that barely stimulate cognitive skills. The implications of the findings are worth considering by technology education lecturers as emphasis should be placed on the pedagogical content knowledge of technology. Amongst others, teacher trainees should grasp the content knowledge, a range of teaching strategies relevant to technology and the nature of technology.